Quorum sensing modulates microbial efficiency by regulating bacterial investment in nutrient acquisition enzymes. (September 2019) - McBride, Steven G.; Strickland, Michael S.
Abstract: Quorum sensing and quenching are components of chemical signaling that microorganisms use for gene regulation. These components regulate extracellular enzyme production and may subsequently mediate microbial efficiency. We performed a 30-day field-based common garden experiment to determine the effect of quorum sensing and quorum quenching on respiration, enzyme activity, and microbial efficiency. For nutrient acquisition enzymes (e.g. n-acetylglucosaminidase), we found that quorum sensing treatments had 1.4–2.2-fold greater activity than quorum quenching treatments. Furthermore, mass-specific respiration for quorum sensing treatments were ∼1.2-fold higher than quorum quenching treatments, indicating lower efficiency. This study highlights soil microbial quorum sensing as a mechanism that influences both enzyme production and mass-specific respiration, and as a potential regulator of enzyme evolutionary-economics. Highlights: Microbial extracellular enzyme activity follows evolutionary economic principles. Quorum sensing regulates the microbial enzyme economy by stimulating production. When quorum sensing is interrupted enzyme production is downregulated.